Chromaffin cell action potentials and their possible role in adrenaline secretion from rat adrenal medulla. - Kidokoro, Y (1980)
1. The role of action potentials in adrenaline secretion was investigated in the rat adrenal medulla. The effects of various treatments on adrenaline secretion from the perfused adrenal medulla were compared with the effects of similar treatments on spike frequency in dissociated adrenal chromaffin cells. 2. KCl concentrations between 10 and 20 mM increased the extracellularly recorded spike frequency of dissociated adrenal chromaffin cells. Upon perfusion by a KCl concentration of 30 mM there was an initial brief burst of spikes followed by a period of inactivity in the continued presence of 30 mM-Kcl. Tetrodotoxin (TTX, 6 microM) decreased the amplitude and frequency of the KCl evoked spikes. 3. The rate of adrenaline secretion from the isolated perfused rat adrenal gland increased as the KCl concentration was raised to 10 and up to 120 mM. Secretion which was evoked by KCl concentrations between 10 and 20 mM was partially inhibited by TTX. At KCl concentrations of 30 mM or greater evoked secretion was no longer affected by TTX. 4. CoCl2 (5 mM) blocked KCl increase of spike frequency and also blocked stimulation of adrenaline secretion by all concentrations of KCl tested. 5. Tetraethylammonium chloride (10 mM), which decreased spike frequency but greatly prolonged the spike duration, enhanced secretion induced by 15 mM-Kcl. 6. The results are consistent with the following interpretation. The TTX insensitive portion of the KCl stimulated adrenaline secretion is due to Ca influx through voltage dependent Ca channels which are open as a consequence of the steady-state level of KCl depolarization. The TTX sensitive portion of secretion is indicative of an extra increment of Ca influx during spike activity enhanced by KCl. This increment of Ca influx may occur through voltage dependent Ca channels whose activation is facilitated by the voltage changes caused during the TTX sensitive Na component of the spike and possibly through the Na channel itself. 7. Stimulation of secretion by acetylcholine (ACh) in the perfused adrenal medulla was half maximal at 15 microM and began to saturate around 50 microM. Release was partially inhibited by TTX only when the concentration of ACh was 10 microM or less. The possible role of action potentials in ACh stimulated adrenaline release is discussed.